2018
DOI: 10.1002/aic.16433
|View full text |Cite
|
Sign up to set email alerts
|

Length‐dependent DNA degradation kinetic model: Decay compensation in DNA tracer concentration measurements

Abstract: DNA is often used as a tracer in both environmental fluid flow characterization and in material tracking to avoid counterfeiting and ensure transparency in product value chains. The main drawback of DNA as a tracer is its limited stability, making quantitative analysis difficult. Here, we study length-dependent DNA decay at elevated temperatures and under sunlight by quantitative PCR and show that the stability of randomly generated DNA sequences is inversely proportional to the sequence length. By quantifying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 34 publications
(50 reference statements)
0
17
0
1
Order By: Relevance
“…Although DNA detectability and concentration from fecal and gut content samples also decreased in longer DNA fragments (Deagle et al, 2006;Kamenova et al, 2018), it was reported that longer eDNA fragments degraded faster after their release into the outer environment in both simulated and empirical studies (Jo et al, 2017;Mikutis et al, 2019;Wei et al, 2018) except Bylemans et al (2018).…”
Section: Liter Ature Re Vie Wsmentioning
confidence: 99%
“…Although DNA detectability and concentration from fecal and gut content samples also decreased in longer DNA fragments (Deagle et al, 2006;Kamenova et al, 2018), it was reported that longer eDNA fragments degraded faster after their release into the outer environment in both simulated and empirical studies (Jo et al, 2017;Mikutis et al, 2019;Wei et al, 2018) except Bylemans et al (2018).…”
Section: Liter Ature Re Vie Wsmentioning
confidence: 99%
“…While constant exposure to UV is unlikely for a DNA storage system, it may reflect a general principle of length-dependent degradation sensitivities. Indeed, other environmental insults exhibit similar length dependencies, with exposure to 90°C thermal treatment leading to nearly 3 orders of magnitude greater degradation for longer strands 28 , while shorter strands were more resilient to freeze-thaw cycles. 29 As these are accelerated degradation studies, it is likely that longer strands will be sufficiently stable for practical use; however, shorter strand lengths would likely provide improved stability profiles.…”
mentioning
confidence: 99%
“…This finding supports the general hypothesis that under well controlled conditions, DNA decay is a random process. [27][28][29][30] Fragmentation results of DNA aged at 30 °C show that nicking the sequence length by one half, approximately. However, no matter how long the resulting fragments are, it may be safely assumed that in a standard sample preparation method involving PCR as initial amplification step, [12][13][14]17 these fragments would not amplify.…”
Section: Resultsmentioning
confidence: 99%
“…This finding supports the general hypothesis that under well controlled conditions, DNA decay is a random process. 2730…”
Section: Resultsmentioning
confidence: 99%